Synthesis and characterization of pH-sensitive conjugate of isoniazid--methoxypoly(ethylene glycol)-b-poly(L-lysine) - Imramovský, Aleš; Grusová, Ludmila; Beneš, Ludvík; Pejchal, Vladimír; Sedlák, Miloš (Bioorganic & medicinal chemistry letters, 2012)
The present paper deals with the preparation and characterization of a conjugate of isoniazid (INH) with the block copolymer methoxypoly(ethylene glycol)-b-poly(L-lysine) (mPEG-b-PLL). The structure of the conjugate (mPEG-b-PLL-INH) was verified by means of (1)H NMR, GPC, infrared spectroscopy, elemental analysis and powder X-ray diffraction. The conjugate contains six l-lysine units with five INH molecules, which are attached by means of pH-sensitive amidine bond. Under in vitro conditions, the conjugate is hydrolyzed and isoniazid is released (pH 4; 37 °C; t(1/2) ≈ 10 h).
Keywords: Isoniazid; Polylysine; Molecular Structure; polylysin; Polyethylene Glycols; Powder Diffraction; polyethylenglykoly; isoniazid; koncentrace vodíkových iontů; prášková difrakce; molekulární struktura; Hydrogen-Ion Concentration